Matrix isolation FT-IR spectroscopy and molecular orbital study of sarcosine methyl ester - Gómez-Zavaglia, Andrea (2004)
N-methylglycine methyl ester (sarcosine-Me) has been studied by matrix isolation FT-IR spectroscopy and molecular orbital calculations undertaken at the DFT/B3LYP and MP2 levels of theory with the 6-311++G(d,p) and 6-31++G(d,p) basis set, respectively. Twelve different conformers were located in the potential energy surface of the studied compound, with the ASC conformer being the ground conformational state. This form is analogous to the dimethylglycine methyl ester most stable conformer and is characterized by a NH...O= intramolecular hydrogen bond; in this form, the ester group assumes the cis configuration and the O=C-C-N and Lp-N-C-C (where Lp is the nitrogen lone electron pair) dihedral angles are ca. -17.8 and 171.3°, respectively. The second most stable conformer (GSC) differs from the ASC conformer essentially in the conformation assumed by the methylamino group, which in this case is gauche (Lp-N-C-C dihedral angle equal to 79.4°). On the other hand, the third most stable conformer (AAC) differs from the most stable form in the conformation of the O=C-C-N axis (151.4°). These three forms were predicted to differ in energy by less than ca. 5 kJ mol-1 and represent [approximate]95% of the total conformational population at room temperature. FT-IR spectra were obtained for sarcosine-Me isolated in argon matrices (T=9 K) revealing the presence in the matrices of the three lowest energy conformers predicted by the calculations. The matrices were prepared by deposition of the vapour of the compound using two different nozzle temperatures, 25 and 60 °C. The relative populations of the three conformers trapped in the matrices were found to be consistent with occurrence of conformational cooling during matrix deposition and with a stabilization of the most polar GSC and AAC conformers in the matrices compared to the gas phase. Indeed, like it was previously observed for the methyl ester of dimethylglycine [Phys. Chem. Chem. Phys. 5 (2003) 52] the different strength of the interactions between the conformers and the matrix environment seem to lead to a change in the relative order of stabilities of GSC and ASC upon going from the gas phase to the matrices, with the first conformer becoming the conformational ground state in the latter media. The assignment of the bands observed in the matrix spectra to the three experimentally observed conformers of sarcosine-Me is presented and discussed.